Aerodynamic Noise Separation of an EMU Trailer Bogie Area Using Train Operation Tests - Leiming Song; Hao Chen; Baochuan Li (Shock and Vibration)
The operation transfer path analysis (OTPA) technique was used to measure the vibration and noise transfer coefficient functions of wheel-rail noise and radiated noise from an electric multiple unit (EMU) train (high-speed train in China) trailer bogie structure to the central area of the trailer bogie for a train running at speeds of 0–5 km/h. By applying these transfer coefficient functions to the noise analysis of high-speed train operation, the contributions of wheel-rail noise and frame-radiated noise to the noise of the bogie area at high speeds are obtained, and the aerodynamic noise is separated from the total noise, providing a reference for vibration damping and noise reduction in high-speed trains. Analysis of test data shows that, in the central area of the trailer bogie of high-speed trains, the low-frequency noise mainly comes from the structural radiated noise of the bogie, and the mid- to high-frequency noise is primarily due to aerodynamic noise. In addition, when an EMU train operates at speeds below 250 km/h, the noise in the central area of the trailer bogie is primarily caused by the structural radiated noise. When the operating speed is higher than 250 km/h, the noise in the central area of the trailer bogie is mainly due to aerodynamic noise, and the aerodynamic noise contribution increases with increase in speed.